Contact activation of coagulation in newly inserted indwelling catheters - Leila Naddi; Caroline Ulfsdotter Nilsson; Karin Strandberg; Thomas Kander (Scientific Reports)
Abstract The aim of this this cross-sectional observational study was to investigate coagulation and platelet activation in blood collected from newly inserted catheters. Blood samples were collected from newly inserted central venous, peripheral venous and arterial catheters in adult patients. Sample 1 was collected within seconds after insertion. Sample 2 was collected directly after Sample 1 but after proper flush and discard. A selected set of haemostatic assays were performed and the results for Sample 1 and 2 compared per catheter type. In total 10 patients per catheter type were included between December 2021 and June 2022. For central venous catheters, there was a difference in ROTEM NATEM clotting time, clot formation time, α-angle, prothrombin time international normalised ratio, factor VII and thrombin–antithrombin complex, supporting strongly enhanced activation in Sample 1 compared to Sample 2. Peripheral venous catheters and arterial catheters were less prone to activate coagulation. In conclusion, our results support flush and discard ahead of haemostatic assay blood sampling in newly inserted catheters. Furthermore, the results enhance the understanding of central venous catheter-related thrombosis formation.